Taktik Usaha Kecil Menengah (UMKM) Dalam Mengantisipasi Kompetisi Bisnis Global: Tinjauan Kasus di PT. Muniru Burni Telong - Rosmaria (PT. Anagata Sembagi Education, 2024)
In Indonesia's economy, Micro, Small, and Medium Enterprises (MSMEs) constitute the largest business segment and have demonstrated resilience against various economic crises. These MSMEs are urged to expand into the global market, not limited to domestic operations alone. The selection of an appropriate strategy is crucial for a company's long-term success in achieving its objectives and gaining a competitive edge. The aim of this study is to determine the most suitable strategy for PT. Muniru Burni Telong, an MSME, in addressing global business competition. The research methodology involves SWOT analysis, as well as IFAS and EFAS, with data collected through interviews, questionnaires, observations, and literature reviews. The findings suggest that PT. Muniru Burni Telong should adopt a strategy in quadrant I, indicative of an aggressive growth approach. This implies that the company is well-positioned to capitalize on available opportunities, demonstrating strength and readiness to expand into targeted markets, foster growth, and achieve significant progress.